Gendered perceptions of workaholism and the gender gap in parenting time. (1st February 2022) - Buchanan, Tom; McFarlane, Adian; Das, Anupam
Abstract : We use the 2015 Canadian time-use survey to analyse predictors of workaholism and the gender gap in parenting time. For mothers, both parenting time and market work are predictive of self-reporting workaholism. Workaholic mothers do not spend less time parenting as their market work increases. These levels remain higher at each level than workaholic fathers and non-workaholic mothers and fathers. This suggests increased market work time does not result in any reduction of relative levels of parenting time. Along with entrenched gendered expectations, mothers may perceive an opportunity cost of sacrificing parenting time for market work. Workaholic mothers do report reduced household labour hours. Accounting for characteristic differences between workaholic mothers and fathers leaves more unexplained than explained. Implications are discussed within the framework of gender and opportunity costs.